KEMANDIRIAN WIRAUSAHA ALUMNI PROGRAM KURSUS HANTARAN DI SKB UNGARAN - Syahna Yustika Almira; Indri Ajeng Setyoningrum (Jurnal Manajemen Pendidikan, 2026)
This study describes the entrepreneurial independence of hantaran course alumni at SKB Ungaran and identifies supporting and inhibiting factors. A descriptive qualitative approach was applied. Data were gathered through in-depth interviews, field observation, and documentation from three purposively selected informants (one instructor, two alumni). Validity was ensured via source and technical triangulation and member checks (Lincoln & Guba, 1985). Analysis followed Miles, Huberman, and Saldana (2014) interactive model. Alumni independence unfolds through four interlocked dimensions—technical skills, entrepreneurial motivation, business management, and business sustainability. Supporting factors include family backing, social networks, and a competency certificate (TUK); inhibiting factors include limited startup capital, seasonal demand, inconsistent digital promotion, and the absence of structured post-training mentoring. This is the first study to examine entrepreneurial independence among hantaran course alumni at a government non-formal education institution, integrating technical, motivational, managerial, and sustainability dimensions within an andragogical lens. Practically, the findings suggest that SKB Ungaran must implement a structured six-month post-training mentoring program and digital marketing training to ensure business sustainability.